Exploring Job Satisfaction and Its Impact on Organizational Commitment and Turnover Intention - Faik, Sinem (Journal of Policy Options, 2023)
This study was conducted with a sample of 100 employees from the production sector and 82 employees from the service sector. The study focuses on exploring the intricate relationships between job satisfaction, organizational commitment, and turnover intention, with the aim of identifying statistically significant associations among these variables. By thoroughly analyzing data from the participants, the research seeks to understand how these factors interact within an organizational setting. The findings strongly support the hypotheses, demonstrating that higher levels of job satisfaction are positively linked to all three dimensions of organizational commitment—affective, continuance, and normative commitment. Specifically, the results indicate that when employees are satisfied with their jobs, they tend to exhibit stronger emotional attachment to their organization (affective commitment), a greater sense of obligation to remain (normative commitment), and a perceived cost of leaving (continuance commitment). On the other hand, turnover intention, or the likelihood of employees wanting to leave the organization, is found to be negatively correlated with both job satisfaction and organizational commitment. This implies that employees who experience high levels of job satisfaction and organizational commitment are less likely to consider leaving their jobs. These findings highlight the importance of fostering a positive work environment where employees feel satisfied and committed, as this can significantly reduce turnover intention and contribute to a more stable and engaged workforce. The implications of the study suggest that organizations aiming to retain talent should focus on enhancing job satisfaction and strengthening organizational commitment across all dimensions.